Photoshop for nature photographers : - Anon, Ellen (Sybex, 2005)
This is the first book to teach nature photographers practical Photoshop skills that will solve their most common problems. Authors Anon and Grey provide a real-world approach that simulates a workshop experience, feature gorgeous photography, and include tips and techniques from the biggest names in nature photography.